2012
DOI: 10.1371/journal.pgen.1002570
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Highly Complex Chemical Resistance Traits across Four Yeast Strains

Abstract: Many questions about the genetic basis of complex traits remain unanswered. This is in part due to the low statistical power of traditional genetic mapping studies. We used a statistically powerful approach, extreme QTL mapping (X-QTL), to identify the genetic basis of resistance to 13 chemicals in all 6 pairwise crosses of four ecologically and genetically diverse yeast strains, and we detected a total of more than 800 loci. We found that the number of loci detected in each experiment was primarily a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
101
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 29 publications
8
101
0
Order By: Relevance
“…This means that while the small-effect alleles are present in both crosses, they are detected only as QTL in the cross containing the interacting alleles of the large-effect QTN. The degree of complexity found in this trait is similar to what has been found elsewhere (Ehrenreich et al 2010(Ehrenreich et al , 2012Parts et al 2011), but the level of epistasis we observe has not previously been established. Our data suggest that the allelic status of large-effect QTL influence the effect sizes of additional genetic variants present in the genome of an individual.…”
Section: Discussionsupporting
confidence: 87%
“…This means that while the small-effect alleles are present in both crosses, they are detected only as QTL in the cross containing the interacting alleles of the large-effect QTN. The degree of complexity found in this trait is similar to what has been found elsewhere (Ehrenreich et al 2010(Ehrenreich et al , 2012Parts et al 2011), but the level of epistasis we observe has not previously been established. Our data suggest that the allelic status of large-effect QTL influence the effect sizes of additional genetic variants present in the genome of an individual.…”
Section: Discussionsupporting
confidence: 87%
“…However, more complex allelic series for QTL in selection pools were also evident. Our results are consistent with previous findings of excess biallelic QTL compared to other allele distributions in F 1 crosses Ehrenreich et al 2012), although this could be affected by the choice of founder strains, crossing design, and mapping approach.Narrow mapping intervals allow rapid causal gene identification QTL mapping in SGRP-4X resulted in narrow regions ripe for following up with single-gene studies. First, we used reciprocal hemizygosity (Steinmetz et al 2002) to test the effects of different IRA1 and IRA2 alleles on growth under heat stress.…”
supporting
confidence: 92%
“…Nineteen of these overlap between ploidies, suggesting that heat-resistance QTL operate largely independently of ploidy, indicating dominant or additive effects and giving additional evidence for the reproducibility of our calls. The mapped regions have a median size of 4.8 kb, a resolution comparable to that expected under linkage mapping and finer than that of bulk segregant analyses in F 1 crosses (Ehrenreich et al 2012).…”
Section: -Segregant F 1 Populations (Cubillosmentioning
confidence: 67%
See 1 more Smart Citation
“…Genetic heterogeneity can reduce the statistical power of mapping studies (Manchia et al 2013;Wray and Maier 2014) and may involve multiple variants segregating in the same gene (allelic heterogeneity) or different genes (nonallelic heterogeneity) (Risch 2000). Work to date has shown that allelic heterogeneity is widespread (e.g., McClellan and King 2010;Ehrenreich et al 2012;Long et al 2014) and often involves two or more null or partial loss-of-function variants segregating in a single phenotypically important gene (e.g., Nogee et al 2000;Sutcliffe et al 2005;Will et al 2010). However, the prominence and underlying mechanisms of nonallelic heterogeneity are less understood.…”
mentioning
confidence: 99%